Suggested models of water harvesting systems: An applied study on the governorates of Al- Mandaq and Bani Hassan - Alzubaidi, Halima Ibrahim (Journal of natural sciences, life and applied sciences, 2022)
The aim of this study is to enhance the water budget in the study area through suggested models of water harvesting systems during precipitation, surface runoff or fog areas, to contribute to the restoration of the strategy of conservation and rationalization of exploitation efficiency through the adoption of small development projects based on the involvement of community members in Development. These proposed methods contribute approximately 58% of the total annual household water requirement, harvesting using rooftops can save about 24%, collecting ponds can save about 9%, and about 20% can be obtained using reservoirs. Ponds behind dams, and fog harvesting method estimated the study could save about 5%. In addition to what can be stored by groundwater wells, and through the leakage of water to the subsoil, which works to achieve sustainable development and recharge of surface aquifers in the study area.
Keywords: water harvesting; precipitation; surface runoff; fog harvesting; dew harvesting